Properties of Hydrochar Derived from Arabica Coffee Agro-Industry Residues under Wet Torrefaction Method - Shalihah, Nyakty; Setiawan, Adi; Muhammad, Muhammad; Riskina, Shafira (Journal of Engineering and Technological Sciences, 2024)
This study utilized coffee cherry residues, which is an abundantly available source of biomass in Indonesia. One of the methods to utilize coffee plantation residues effectively is wet torrefaction. This method is well-known as a hydrothermal method, where the biomass conversion process uses liquid as a medium and reactant in the process. The objective of this work was to develop an effective procedure for converting coffee agro-waste into marketable products using hydrothermal technology. The information related to changes in physical and thermal properties were explored in this work. To achieve the research objectives, three main steps were performed, i.e., feedstock preparation, wet torrefaction, and hydrochar characterization. Two types of feedstocks were studied in this work, coffee parchment and coffee pulp. In the wet torrefaction process, each feedstock was treated using two types of solutions, i.e., distilled water and acetic acid, at different concentrations. The reaction was carried out in an autoclave with a pressure of 2 bar (g) and an operating temperature of 130 ℃ for 2 hours. The properties of the hydrochar products were then analyzed using various methods, including bomb calorimetry, SEM, density, TGA-DTG, and hydrophobicity analyses. Overall, the results indicated that the hydrochar produced under acetic acid solution had better characteristics compared to that treated under distilled water. In terms of fixed carbon content and calorific value, the values increased up to 25.3% and 4,603 kcal/kg, respectively. Enhanced hydrophobicity was only observed in the coffee parchment hydrochar, where the average time required to adsorb water was 146.6 s, which can be categorized as strongly hydrophobic.